Adiponectin ameliorates experimental periodontitis in diet-induced obesity mice. - Lan Zhang; Shu Meng; Qisheng Tu; Liming Yu; Yin Tang; Michel M Dard; Sung-Hoon Kim; Paloma Valverde; Xuedong Zhou; Jake Chen (PLoS ONE, 2014)
Adiponectin is an adipokine that sensitizes the body to insulin. Low levels of adiponectin have been reported in obesity, diabetes and periodontitis. In this study we established experimental periodontitis in male adiponectin knockout and diet-induced obesity mice, a model of obesity and type 2 diabetes, and aimed at evaluating the therapeutic potential of adiponectin. We found that systemic adiponectin infusion reduced alveolar bone loss, osteoclast activity and infiltration of inflammatory cells in both periodontitis mouse models. Furthermore, adiponectin treatment decreased the levels of pro-inflammatory cytokines in white adipose tissue of diet-induced obesity mice with experimental periodontitis. Our in vitro studies also revealed that forkhead box O1, a key transcriptional regulator of energy metabolism, played an important role in the direct signaling of adiponectin in osteoclasts. Thus, adiponectin increased forkhead box O1 mRNA expression and its nuclear protein level in osteoclast-precursor cells undergoing differentiation. Inhibition of c-Jun N-terminal kinase signaling decreased nuclear protein levels of forkhead box O1. Furthermore, over-expression of forkhead box O1 inhibited osteoclastogenesis and led to decreased nuclear levels of nuclear factor of activated T cells c1. Taken together, this study suggests that systemic adiponectin application may constitute a potential intervention therapy to ameliorate type 2 diabetes-associated periodontitis. It also proposes that adiponectin inhibition of osteoclastogenesis involves forkhead box O1.